Empowering Persons with Disabilities through Inclusive Productive Zakat Models: Insights from Indonesian Local Cases - Budi Santoso, Aditya; Nurhadi, Agus; bin Ghazali Mohd Jani, Mohd Hiriy (UIN Sunan Kalijaga, Yogyakarta, Indonesia, 2025)
The process of empowerment through the collection of charitable resources for individuals with disabilities is predominantly associated with economic factors. Nonetheless, the distribution of zakat plays a pivotal role for beneficiaries (mustaḥiqq), emphasizing inclusive models rather than productive approaches. To explore these dynamics, the researchers conducted fieldwork in Rowosari Village, Semarang City, Indonesia. Data were collected through in-depth interviews with representatives from relevant institutions and disability advocacy groups, employing a phenomenological analytical framework. The findings reveal that zakat institutions, such as Darut Tahuhid Peduli, have implemented the Indonesia Peduli Difabel initiative, which focuses on sustainable economic empowerment, entrepreneurial training, and community integration. These programs have demonstrated success in planning, assessment, distribution, assistance, and evaluation. Consequently, a bottom-up model for empowering individuals with disabilities has emerged, facilitating the development of pertinent business models, such as catfish farming, through the verification of beneficiaries’ eligibility and the execution of feasibility studies. The initiatives are effectively utilizing allocated zakat funds in aquaculture and financial management. Continuous support is provided to assist individuals with disabilities in both economic and personal development. This research not only addresses material considerations but also incorporates social and spiritual dimensions as mechanisms for empowerment that positively influence personal well-being. Thus, this article contributes to the advancement of knowledge regarding welfare provision discourses, aligning with additional elements that enhance empowerment studies.